Penatalaksanaan Holistik Pada Wanita Lanjut Usia Dengan Katarak Melalui Pendekatan Kedokteran Keluarga di Wilayah Puskesmas Karang Anyar - akhlish dzikrullah ahmad; Diana Mayasari (Majority, 2022)
Cataracts are the cause of blindness which accounts for approximately half of all blindness in the world, especially in developing countries. This is because in developing countries the level of knowledge related to this disease is still low. Awareness of the importance of checking eye health regularly is still low. From this figure, cataract is the highest cause of blindness, about 81 percent. The method used is case report. Primary data were obtained through autoanamnesis and alloanamnesis, physical examination and home visits, to complement family data, psychosocial and environmental data. Assessment is carried out based on a holistic diagnosis from the beginning, process, and end of the study qualitatively. Based on a holistic diagnosis, it was found that an 88-year-old patient complained of wanting to check the condition of his right and left eyes because there was foggy vision in both eyes, the right eye looked more foggy than the left. On eye localis status, eye examination found: The lens of the right eye is cloudy, mature, with a shadow test - with 6/20 vision, and the left eye is immature cloudy with a shadow test + with a vision of 1/60. Internal risk factors in the form of lack of sufficient knowledge of the disease he suffered. The evaluation results showed a strong desire to perform cataract surgery and awareness of the importance of therapy for hypertension. Cases of elderly patients in the form of cataracts and hypertension. Selecting the patient's daughter-in-law as PMO and patient companion. Mrs. M has dared to perform cataract surgery. The patient's management, namely lens extraction, was appropriate. There has been a change in knowledge of Mrs. M, Mr. H, Mrs. U, and Mr. S regarding the disease suffered by the patient and how to respond to it because of the counseling carried out by the researcher.